Transmedia Narrative as an Experience of Collective Intelligence Simulation. The case of Atrapados (Trapped) - Rodríguez Ruíz, Jaime Alejandro (Pontificia Universidad Javeriana - Facultad de Comunicación y Lenguaje, 2015)
This article describes and analyzes the transmedia experience of the research project “Simulator IC, a transmedial test scenario for the simulation of collective intelligence”, in which the ability of four fictional artifacts was explored, —literary text, comic, videogame and role-playing game— generated from the transmediation of a literary source to develop sensitivity in resolving problems with characteristics linked to collective intelligence. The research method was mixed, with a main qualitative component and a quantitative one —observational methodology—. When a measurement of the collective intelligence gradient of the participants was performed upon contact and interaction with various problem simulation strategies —artifact combination according to a specific experimental design—, it was found that the complete transmedia experience, ie. Interaction with the four artifacts, enhances the effects and benefits the simulation with individual artifacts.